On hyper BCC-algebras - R. A. Borzooei; W. A. Dudek; N. Koohestani (International Journal of Mathematics and Mathematical Sciences)
We study hyper BCC-algebras which are a common generalization of BCC-algebras and hyper BCK-algebras. In particular, we investigate different types of hyper BCC-ideals and describe the relationship among them. Next, we calculate all nonisomorphic 22 hyper BCC-algebras of order 3 of which only three are not hyper BCK-algebras.